A comparison of family and nonfamily small firms in their approach to green innovation: A study of Italian companies in the agri‐food industry. (18th June 2019) - Dangelico, Rosa Maria; Nastasi, Alberto; Pisa, Simone
Abstract: Despite the growing scholars' attention toward green innovation, on the one hand, and family firms, on the other hand, there is still limited attention toward the intersection of these two streams of literature, because very few studies deal with green innovation in family firms. This paper aims at comparing family and nonfamily small firms in their approach to green innovation. To this aim, a multiple case studies methodology was used to understand whether and in which aspects family firms and nonfamily firms differ. In particular, a sample of 14 small enterprises (seven family and seven nonfamily firms) operating in the agri‐food industry and located in Italy was studied. Results suggest that family and nonfamily firms are similar with regard to green innovation characteristics, features of the green innovation process, faced challenges, and achieved outcomes. On the contrary, family firms differ from nonfamily firms in three key areas: firm's motivations, most relevant pressures, and green innovation view.